Arctic shadow [large type] - Sundell, Joanne (Watch eyes trilogy, 2016)
After a sled dog is killed in 1909 Alaska, fourteen-year-old Anya, a Chukchi shaman, and seventeen-year-old Rune must battle dark spirits born of inhuman evil.